Therapy-related myelodysplastic syndrome presenting as fulminant heart failure secondary to myeloid sarcoma - Matkowskyj, Kristina A. (Springer-Verlag, 2010)
Rapidly progressive heart failure is commonly caused by an extensive myocardial infarction, a mechanical complication of infarction, myocarditis, or acute valvular insufficiency. We present an unusual case that was caused by a diffuse infiltration of the myocardium with leukemic cells (myeloid sarcoma). The patient presented with episodic shortness of breath, he was anemic and thrombocytopenic, and his bone marrow biopsy revealed myelodysplastic syndrome from treatment for oligodendroglioma. His clinical course was characterized by a chronic leak of cardiac enzymes, a new right bundle branch block, and a large pericardial effusion causing tamponade and death from fulminant heart failure and ventricular arrhythmias within 2 weeks. At autopsy, the heart was massively infiltrated with myeloblasts and other immature myeloid cells. There was no evidence of acute leukemia in the bone marrow or peripheral blood. Cardiac infiltration in a patient with myelodysplastic syndrome is extremely rare, especially in the absence of bone marrow involvement by blasts. The recognition of this entity is becoming increasingly important as the incidence of cardiac myeloid sarcoma may be on the rise as the number of patients receiving chemotherapy increases.